The Use of Augmeted Reality as an Innovative Learning Media for Fiqh Material - Afit Datul Musafa'ah; Andryadi Andryadi; Mu’alimin Mu’alimin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
In the process of knowledge transfer, innovation in learning media is needed to understand the context of fiqh material, to support teachers in delivering teaching content. In line with the 21st century, collaboration between education and technology is required, resulting in many breakthroughs in modern learning media. Augmented Reality is an additional reality in the form of advanced technology that combines virtual objects and real objects directly. This study aims to develop innovative learning media in the form of valid flash cards, the use of media, and the impact of using these flash cards. This type of research is research and development (R&D) using the ADDIE model, which consists of the following steps: Analysis, Design, Development, Implementation, and Evaluation. The development of the media went through a feasibility test by media experts, subject matter experts, practitioners (subject teachers), small group trials, and large group trials (students) with the distribution of questionnaires. The research was conducted in class X of Madrasah Aliyah Wali Songo with a total of ten students. The results show that the flash card learning media recapitulation meets the validity test with a score of 86,22% by media experts, 88,57% by fiqh lecturers, 85% by learning practitioners (teachers), 87.6% in small group trials, and 90% in large group trials, resulting in an average percentage score of 87.62% (very good for use). It can be concluded that the development of this media is able to increase student motivation and engagement, create enjoyable learning, improve understanding of fiqh munakahat material, and can certainly be used by teachers to innovate learning media in the classroom